2018
DOI: 10.1080/09273948.2017.1420203
|View full text |Cite
|
Sign up to set email alerts
|

Complications in Intermediate Uveitis: Prevalence, Time of Onset, and Effects on Vision in Short-Term and Long-Term Follow-Up

Abstract: IU is a chronic low-grade uveitis that may be associated with protean early and late complications of the anterior or posterior segments or both. Optimal treatment regimens are imperative for the strict control of inflammation and proper management of complications thus allowing a favorable long-term prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 13 publications
4
15
0
Order By: Relevance
“…The previous studies showed that uveitis, especially chronic uveitis, would lead to band keratopathy. 20,21 Nevertheless, the inflammatory process in uveitis that involves cytokine alteration such as IL-6 and TNF may influence the corneal condition, 17 because the use of cyclosporine that suppresses interleukin activity can relieve some categories of keratopathies. 22 Moreover, the corneal endothelial cells were damaged with an altered central corneal thickness in patients with uveitis, [14][15][16]23 whereas inflammatory cell infiltration into the corneal stoma was also observed during the onset of anterior uveitis.…”
Section: Discussionmentioning
confidence: 99%
“…The previous studies showed that uveitis, especially chronic uveitis, would lead to band keratopathy. 20,21 Nevertheless, the inflammatory process in uveitis that involves cytokine alteration such as IL-6 and TNF may influence the corneal condition, 17 because the use of cyclosporine that suppresses interleukin activity can relieve some categories of keratopathies. 22 Moreover, the corneal endothelial cells were damaged with an altered central corneal thickness in patients with uveitis, [14][15][16]23 whereas inflammatory cell infiltration into the corneal stoma was also observed during the onset of anterior uveitis.…”
Section: Discussionmentioning
confidence: 99%
“…10 In another study of patients with intermediate uveitis, the most common complications were cystoid macular edema, cataracts, and posterior synechia, and glaucoma was also noted. 11 The pathogenesis of secondary VPRT associated with intermediate uveitis is believed to involve a reactive process against factors released into the environment with the emergence of uncontrolled proliferation of fibrous tissue and angiogenesis in the retina secondary to disruption of the blood-retina barrier. 2 On the other hand, it has also been suggested that the presence of intraocular inflammation and uveitis may be due to a reactive, or "spillover" phenomenon in which inflammatory cells leak from tumoral lesion vessels into the vitreous.…”
Section: Discussionmentioning
confidence: 99%
“…Intermediate uveitis with its centre of inflammation in the vitreous body and peripheral retina anterior to the equator usually occurs as pars planitis as a disease in its own right and much more rarely in the scope of sarcoidosis (including Blau syndrome) or juvenile multiple sclerosis [8]. Even though both aforementioned underlying diseases combined occur in less than 10 [10].…”
Section: Intermediate Uveitismentioning
confidence: 99%
“…It occurs mostly occurs on both sides and must not necessarily appear as granulomatous inflammation in all cases [13]. In terms of treatment, the focus is on systemic steroids in 64 % of children; steroid-sparing drugs (MTX, ciclosporin, TNF inhibitors and mycophenolate) are used in 42 % [8].…”
Section: Intermediate Uveitismentioning
confidence: 99%